Effect of Earning Opacity on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange - Kaharuddin Kaharuddin; Abdul Rahman Mus; Muh Su’un (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2022)
The Effect of Earning Opacity on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2018–2020 period. This study aims to determine the effect of Earning Opacity on Tax Avoidance in manufacturing companies listed on the Indonesian stock exchange. This research is a quantitative research using an explanatory approach, namely to see the causal relationship between the dependent variable and the independent variable. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the period 2018 - 2020 as many as 177 then those that met the sample criteria were 26 companies which were taken based on purposive sampling criteria, so that the company sample data were 78 companies (a period of 3 years). SPSS test tool for windows 24.00. The test results show that earning aggressiveness has a negative and insignificant effect, earning smoothing has a positive and significant effect, loss avoidance has a negative and insignificant effect on Tax Avoidance.